The coexistence of two rare diseases thought to use the same pathologic pathway: cystic fibrosis and Niemann-Pick disease - Yılmaz, Aslı İmran; Uğurlu, Betül; Ünal, Gökçen; Tokgöz, Hüseyin; Pekcan, Sevgi (The Turkish Journal of Pediatrics, 2022)
Background. Cystic fibrosis (CF) is a multisystemic, autosomal recessive disease, which is caused by a mutation in the transmembrane conduction regulator protein (CFTR) gene. We present a patient who was diagnosed with CF and later diagnosed with Niemann-Pick type-A (NPA) disease, which is an autosomal recessive lysosomal lipid storage disease. Case. A 2-month-old Syrian refugee patient was diagnosed with CF due to a high sweat test and two homozygous CFTR-related pathogenic gene mutations in our pediatric pulmonology clinic, where she was referred due to a high immunoreactive trypsinogen (IRT) value as a result of newborn screening. As the patient had neurological symptoms and hepatosplenomegaly that could not be explained by CF in the clinical follow-up, the patient was diagnosed with NPA was made with a cherry red spot on eye examination, foam cells in the bone marrow, and low sphingomyelinase activity, in addition to CF. Conclusions. Although CF and NP have common systems of involvement in both diseases, pathological symptoms have different origins. If a patient with CF has simultaneous neuromotor delay, other autosomal recessive diseases that may accompany it should be suspected. In studies, similar pathological pathways related to abnormal cholesterol accumulation in the cell were detected between NP type C and CF. But our case was NPA. As case reports on the coexistence of the two diseases increase, we believe that a better understanding of similar pathological pathways may lead to new therapeutic targets for both diseases.
Keywords: Niemann-Pick; autosomal recessive diseases; cystic fibrosis; pathological pathway